2017
DOI: 10.1002/admt.201600228
|View full text |Cite
|
Sign up to set email alerts
|

Recyclable Nonfunctionalized Paper‐Based Ultralow‐Cost Wearable Health Monitoring System

Abstract: In recent years, innovation in wearable health monitors has surged from significant 30 advances in flexible sensory arrays, wireless technologies, and scaled low-power electronics. Such 31 biometric monitoring devices are critical for continuous monitoring of body vitals and health 32 conditions as means of care for advanced personalized healthcare. Still, widespread deployment of 33 such devices are far more remote due to affordability (viz. complex materials and processes induced 34 higher price), low sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 26 publications
0
50
0
Order By: Relevance
“…The salt water drops had no effect on the output of the sensor. The momentary drop in capacitance was due to the proximity of the hand holding the pipette full of salt water [56][57][58]. The capacitance returns its original value after the hand is moved away from the sensor.…”
Section: Bending Pressure Temperature and Humidity Testingmentioning
confidence: 99%
“…The salt water drops had no effect on the output of the sensor. The momentary drop in capacitance was due to the proximity of the hand holding the pipette full of salt water [56][57][58]. The capacitance returns its original value after the hand is moved away from the sensor.…”
Section: Bending Pressure Temperature and Humidity Testingmentioning
confidence: 99%
“…In recent years, flexible electronics have been extensively investigated to break through the intrinsic limitations of rigid electronics, leading to the realization of unprecedented form factors for unconventional user experiences . This is because of the lightweight, portable, and human‐friendly interface characteristics of the flexible devices.…”
Section: Flexible Memristive Devicesmentioning
confidence: 99%
“…Their goal is mainly to reduce the cost and manufacturing complexity of LOC devices, but unique beneficial characteristics have also been revealed, such as the mechanical flexibility of the LOC platform. Due to its accessibility, flexibility, and desired porosity, which leads to enhanced sensitivity and faster fluid flow (namely, reduced surface tension), paper has been extensively studied and used as a host platform and active material for several types of LoC devices, including sensors, actuators, microfluidic devices, and health monitoring and diagnostic systems . Therefore, interest in paper‐based LOC devices has been significantly increasing as they display the potential to be faster, cheaper, and more multiplexed than the current analysis systems …”
Section: Paper‐based Systemsmentioning
confidence: 99%
“…Similarly, Whitesides and co‐workers demonstrated the development of micro total analysis systems on paper, where printed electronics and microfluidic structures are integrated into a stacking assembly, along with the incorporation of off‐the‐shelf IC components for system functionality . In a subsequent study, Nassar et al further showed the successful integration capability of paper‐based sensors into a fully autonomous and wearable ultralow‐cost medical diagnostic system, referred to as the “Paper Watch,” capable of continuously monitoring various vital signs such as heart rate, blood pressure, body temperature, and skin hydration …”
Section: Paper‐based Systemsmentioning
confidence: 99%